Integrated multi-trophic culture of Penaeus vannamei with Gracilaria domingensis in biofloc system - Santos, Elizabeth Pereira; Lima, Priscilla Celes Maciel de; Oliveira , Carlos Yure Barbosa; Silva , Débora Louise Barros; Oliveira, Deyvid Willame Silva; Brandão , Barbara de Cassia Soares; Brito, Luis Otavio; Gálvez, Alfredo Olivera (Acta Scientiarum. Biological Sciences, 2025)
Co-cultures of the Pacific white shrimp Penaeus vannamei and seaweeds have been proposed as a promising and environmentally friendly way to reduce the levels of nitrogen and phosphorus in aquaculture wastewater. Therefore, the aim of this study was to evaluate the interaction between protein levels in feed as well as the stocking densities of the seaweed Gracilaria domingensis in an integrated culture with P. vannamei using biofloc system. To do so, two protein levels in feed (32% and 40% of crude protein) and four stocking densities (0, 2.5, 5.0, and 7.5 kg m−3) of G. domingensis integrated with P. vannamei were evaluated at the secondary nursery phase, in factorial design (2-factor ANOVA). Shrimp (0.5 ± 0.05 g) were stocked at a density of 500 shrimp m−3 and reared for 42 days. During the experiment, water quality analysis was conducted, and at the end growth performance was evaluated. The water quality was not influenced by both factors, showing no significant differences. Regarding growth performance, the survival (86.2 ± 10.1%) and protein utilization efficiency rate (1.8 ± 0.3) did not differ among treatments. Feed conversion rate, weekly growth, and yield were influenced by protein percentage of the feed, presenting higher values when fed with 40% feed. However, the final mean weight of the shrimp integrated with the seaweed with 32% crude protein supply was similar to the monoculture treatment with 40% crude protein. In summary, the addition of G. domingensis in an integrated culture with P. vannamei did not affect shrimp performance.